2013
DOI: 10.1073/pnas.1315179111
|View full text |Cite|
|
Sign up to set email alerts
|

Functional traits explain variation in plant life history strategies

Abstract: Significance Plants have evolved diverse life history strategies to succeed in Earth’s varied environments. Some species grow quickly, produce copious seeds, and die within a few weeks. Other species grow slowly and rarely produce seeds but live thousands of years. We show that simple morphological measurements can predict where a species falls within the global range of life history strategies: species with large seeds, long-lived leaves, or dense wood have population growth rates influenced primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
533
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(559 citation statements)
references
References 56 publications
18
533
1
7
Order By: Relevance
“…Our results demonstrated that the scaling relationship of N and P was significantly different between herbaceous and woody species in response to environmental variations. Compared to woody species, herbaceous species were characterized by quick growth, high leaf nutrient contents, and fast life histories (Adler et al 2014;Grime 1977). In our study, herbaceous species exhibited a flatter scaling slope in the stems and roots with increased elevation, which implied a faster declination of P than N. In order to survive in low-nutrient habits, herbaceous species might ensure the nutrient supply of the leaves at the expense of declining P allocation to the stems and roots.…”
Section: Conservatism Of N and P Scaling Relationship In Leaves Stemmentioning
confidence: 62%
“…Our results demonstrated that the scaling relationship of N and P was significantly different between herbaceous and woody species in response to environmental variations. Compared to woody species, herbaceous species were characterized by quick growth, high leaf nutrient contents, and fast life histories (Adler et al 2014;Grime 1977). In our study, herbaceous species exhibited a flatter scaling slope in the stems and roots with increased elevation, which implied a faster declination of P than N. In order to survive in low-nutrient habits, herbaceous species might ensure the nutrient supply of the leaves at the expense of declining P allocation to the stems and roots.…”
Section: Conservatism Of N and P Scaling Relationship In Leaves Stemmentioning
confidence: 62%
“…For instance, if important traits are constant within species, it could be possible to build trait databases for species and then predict ecosystem services by knowing which species are present, using previously recorded trait data (Box 2). To meet similar data needs in the broader field of ecology, advances have been facilitated by large-scale, coordinated collection and aggregation of trait data [69][70][71][72]. Ecologists working in agroecosystems should also establish a universally accessible agricultural trait database for all species in agroecosystems, across taxa, farm management, and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in functional traits illustrates how species acquire and utilize resources to grow, reproduce, and tolerate herbivores, pathogens, and mechanical damage (Adler et al 2013;Chave et al 2009;Onoda et al 2011;Reich et al 1997;Wright et al 2004). In general, species with low leaf mass area (LMA), high foliar N content, short leaf lifespans, and low wood density rapidly convert light energy to carbon, and thus growth, at the cost of greater susceptibility to herbivore and pathogen attacks and reduced shade and drought tolerance (Adler et al 2013;Reich 2014;Reich et al 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Variation in functional traits illustrates how species acquire and utilize resources to grow, reproduce, and tolerate herbivores, pathogens, and mechanical damage (Adler et al 2013;Chave et al 2009;Onoda et al 2011;Reich et al 1997;Wright et al 2004). In general, species with low leaf mass area (LMA), high foliar N content, short leaf lifespans, and low wood density rapidly convert light energy to carbon, and thus growth, at the cost of greater susceptibility to herbivore and pathogen attacks and reduced shade and drought tolerance (Adler et al 2013;Reich 2014;Reich et al 1997). Conversely, species with trait values associated with resource conservation, e.g., high LMA, low foliar N content, long leaf lifespans, and high wood density, utilize resources to conserve carbon or water by investing in structures that decrease susceptibility to abiotic and biotic stressors, which results in slower growth but greater shade and drought tolerance (Adler et al 2013;Reich 2014;Reich et al 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%